Evaluating the Impact of Medicaid Expansion on Pharmacy Access and Health Outcomes - Nanda, Naimish; Syed Sabir Ali, Syed Sajid Ali (Journal of Neonatal Surgery, 2025)
Any noxious and unintended response to a drug that occurs at doses used in man for the prophylaxis, diagnosis or therapy of disease, or for the modification of physiological function" is how the World Health Organization defines an adverse drug reaction (ADR). Adverse drug responses, or ADRs, are undesirable or harmful side effects of a medication. In addition to drug factors like drug type, dosage, length of treatment, co-ingestion of other drugs, and route of administration, patient characteristics like age, gender, body weight, coexisting diseases, ethnicity, genetics, or geography also affect the frequency and severity of adverse drug reactions (ADRs). The purpose of this project is to identify, assess, manage, document, and share adverse drug responses. The current investigation determined the ADR pattern that the patients on ATT experienced. The incidence of ADRs was greater in males. The most frequent ADRs were related to the gastrointestinal tract. The majority of ADRs had a "possible" link with the implicated medications, according to an assessment of their causality. The majority of ADRs had "mild" severity. During the trial period, no serious, life-threatening adverse drug reactions were noted. For pupils to do well, procrastination is essential. The reviews of previous studies by researchers are included in the second chapter. The third chapter also provides examples of the study's methodology, which will outline the subjects being examined and the selection process for them. Additionally, the substance of the instrument that will be used to gather information will be described. Analyzing links or differences, separating or comparing with original or new hypotheses, and applying statistical tests of significance are all part of the fourth chapter, which aims to ascertain the validity of the data used to support any conclusions. The research conclusion is the final chapter.